2005
DOI: 10.1212/01.wnl.0000180910.72487.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiepileptic medication on bone mineral measures

Abstract: Patients using AEDs for > 2 years, in particular those taking enzyme-inducing AEDs and those older than 40 years, have significantly lower bone mineral density at clinically relevant fracture risk sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 28 publications
1
49
0
4
Order By: Relevance
“…AEDs increase catabolism of 25-hydroxyvitamin D by induction of the hepatic P-450 enzyme system, leading to relative hypocalcemia, increased levels of parathyroid hormone (PTH), and subsequent low BMD (Dent et al, 1970;Keck et al, 1982;Chung and Ahn, 1994). However, some studies have suggested a significant reduction in BMD with non-enzymeinducing AEDs (Oner et al, 2004;Petty et al, 2005). Other environmental and epidemiological parameters including age, sex, diet, and mobility may also affect mineral metabolism (Pack and Morrell, 2001), suggesting a multifactorial etiology.…”
Section: Introductionmentioning
confidence: 99%
“…AEDs increase catabolism of 25-hydroxyvitamin D by induction of the hepatic P-450 enzyme system, leading to relative hypocalcemia, increased levels of parathyroid hormone (PTH), and subsequent low BMD (Dent et al, 1970;Keck et al, 1982;Chung and Ahn, 1994). However, some studies have suggested a significant reduction in BMD with non-enzymeinducing AEDs (Oner et al, 2004;Petty et al, 2005). Other environmental and epidemiological parameters including age, sex, diet, and mobility may also affect mineral metabolism (Pack and Morrell, 2001), suggesting a multifactorial etiology.…”
Section: Introductionmentioning
confidence: 99%
“…5 A study revealed that AED use was associated with reduced BMD in 35 pairs of twin adults, and the effect was more marked in those prescribed enzyme-inducing AEDs, for example, phenytoin and phenobarbitone. 6 A decrease in BMD (in g/cm 2 ) of 6.4% and 4.6% at the lumbar spine and femoral neck respectively in their twin control pair was detected. For valproate, the effect was not consistently demonstrated.…”
Section: Discussionmentioning
confidence: 86%
“…De plus, la phénytoïne et certains barbituriques inhiberaient directement l'absorption intestinale du calcium [35]. Cela explique pourquoi l'évaluation systématique de la réserve vitaminique D et sa correction sont fréquemment recommandées lors de tout traitement anticonvulsivant [36].…”
Section: Anticonvulsivantsunclassified